(untitled) (Bangladesh Journal of Medical Biochemistry, 2018)
The growing burden of hypertension and type 2 diabetes mellitus (T2DM) in Nigeria and related cardiovascular complications is becoming a public health concern. Cardiovascular risk factors were evaluated in control subjects (n=150) and patients (n=470) [hypertensive nondiabetics (n=179), normotensive diabetics (n=132), hypertensive diabetics (n=159)] attending at the Medical Out-Patient Clinic of the State Hospital, Abeokuta, Nigeria. Cholesterol, triacylglycerols and phospholipids were determined spectrophotometrically in plasma, erythrocytes and lipoproteins. The presence of either or both diseases resulted in significant (p<0.05) perturbations in blood lipids of the male and female patients. Dyslipidemia was characterised by increased concentrations of cholesterol and triacylglycerols in plasma, erythrocytes, low density lipoprotein (LDL) and very low-density lipoprotein (VLDL). The increase was more pronounced in hypertensive diabetics. High density lipoprotein (HDL) cholesterol values of the male and female patients were between 35% to 43% and 37% to 43% respectively lower than their control counterparts, while that of HDL triacylglycerols was between 8% to 10% and 6% to 23% respectively lower than their control counterparts. Plasma and erythrocyte phospholipid content increased significantly (p<0.05) in all the patients when compared with their control counterparts except in the erythrocytes of the normotensive diabetic male, where significant decrease was observed. Our findings suggest that enhanced hypercholesterolemia, hypertriacylglycerolemia and hyperphospholipidemia in plasma and erythrocytes may be responsible for increased cardiovascular complications in the comorbidity since the combined dyslipidemia are more pronounced in comorbidity of hypertension and T2DM than when either of the two conditions occurs in isolation. Bangladesh J Med Biochem 2017; 10(2): 45-57